PERANAN HAKIM DALAM MEMBERIKAN NASEHAT KEPADA PENGGUGAT ATAS GUGATAN YANG KABUR TERHADAP PERKARA SENGKETA TANAH - Sari, Natalia Andita; Ramlani Lina Sinaulan,; Achmad Fitrian, (Journal of Innovation Research and Knowledge, 2023)
As there are still many plaintiffs who make their lawsuit categorized as vague/unclear, it is deemed necessary that the role of the Judge/Chair of the District Court in helping direct the obscure lawsuit made by the Plaintiff, thus facilitating the civil case proceedings even though the Judge is passive. The purpose of this study is to analyze the role of the Judge in providing advice to the plaintiffs for an obscure lawsuit in land dispute cases. This research method is a case study with Decision Number 908/Pdt.G/2018/PN.Tng. The results showed that the Head of the Tangerang District Court was considered quite optimal according to Article 119 HIR or Article 143 RBg, although the Head of the PN has a passive rule and function. Factors affecting the Head of the PN in providing advice and assistance to the plaintiff in civil cases include the relative authority of the District Court as regulated in Article 4 paragraph (2) of the Law on Judicial Powers.